Radioisotope scanning of the lungs. Issue 1 (January 1968) - Bell, T. K.; Ferguson, R.; McIlrath, E. I.; Weaver, J. A.
Abstract : Lung scanning with macroaggregated albumin 131 I was carried out in 128 patients. The technique appears to be without hazard. It is particularly useful in the detection of pulmonary embolism, but the pattern is non-specific and changes occur in other cardio-respiratory diseases. On the basis of these observations pulmonary scanning is regarded as a useful adjunct in the study of pulmonary embolism, but it cannot serve as a specific diagnostic procedure since similar patterns of scan may be found in many conditions.